The role of intangible metrics in achieving sustainable development goals - Aracelly Fernanda Núñez-Naranjo; Ana Córdova-Pacheco; Santiago Chicaiza-Moreta (Heritage and Sustainable Development)
The fulfillment of the Sustainable Development Goals at a global level must be approached from the perspective of human, structural and employee capital, because their fulfillment stems from the productivity that stands out in the observation of intangible metrics. The research focuses on investigating how intangible metrics contribute to the financial performance of companies listed on the Quito Stock Exchange (BVQ), as well as determining how SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation and Infrastructure) are affected by the results of the measurement of intangible metrics. Sixty-seven companies are considered which have been studied in the calculation of the Value-Added Intellectual Value (VAIC), to evaluate the intangible metrics on the other hand the calculation of return on assets (ROA) and return on equity (ROE). Results show that capital employed, and structural capital have an impact on profitability (ROA) and (ROE), however, human capital did not have an effect on the variable. It can be concluded that the importance of inquiring about structural capital and capital employed in the performance of companies is emphasized, since this contributes to the fulfillment of sustainability, which are contributing to the fulfillment of the (SDGs).